Solution effects on the self‐association of a water‐soluble peptoid. Issue 4 (22nd December 2018) - Fuller, Amelia A.; Huber, Jonathan; Jimenez, Christian J.; Dowell, Kalli M.; Hough, Samuel; Ortega, Alberto; McComas, Kyra N.; Kunkel, Jeffrey; Asuri, Prashanth
Abstract: A desire to replicate the structural and functional complexity of proteins with structured, sequence‐specific oligomers motivates study of the structural features of water‐soluble peptoids ( N ‐substituted glycine oligomers). Understanding the molecular‐level details of peptoid self‐assembly in water is essential to advance peptoids' application as novel materials. Peptoid 1, an amphiphilic, putatively helical peptoid previously studied in our laboratory, shows evidence of self‐association in aqueous solution. In this work, we evaluate how changes to aqueous solution conditions influence the self‐association of 1 . We report that changes to pH influence the fluorescence and CD spectroscopic features as well as the peptoid's interaction with a solvatochromic fluorophore and its apparent size as estimated by size exclusion chromatography. Addition of guanidine hydrochloride and ammonium sulfate also modulate spectroscopic features of the peptoid, its interaction with a solvatochromic fluorophore, and its elution in size exclusion chromatography. These data suggest that the ordering of the self‐assembly changes in response to pH and with solvent additives and is more ordered at higher pH and in the presence of guanidine hydrochloride. The deeper understanding of the self‐association of 1 afforded by these studies informs the design of new stimuli‐responsive peptoids with stable tertiary or quaternary structures. Abstract :